Improvement of frozen poultry storage technology - Онищенко, В’ячеслав Миколайович; Гринченко, Наталя Геннадіївна; Большакова, Вікторія Анатоліївна (Eastern-European Journal of Enterprise Technologies, 2015)
The most effective and most common method to solve the problem of preserving the quality and safety of poultry during long-term storage is freezing. However, from the technological and commercial points of view, freezing of poultry causes some irreversible changes that make it impossible to fully restore its original characteristics and accordingly functional and technological and consumer properties after defrosting. A promising way to minimize negative effects of low temperatures is the use of cryoprotectants - the substances that prevent or slow down the growth of ice crystals during freezing. The dependence of the viscosity of solutions of selected polysaccharides on their concentration to be used as solutions for pumping was determined. Considering the equipment requirements, including the probability of the injector needle clogging, the xanthan gum concentration of 0.5%, which corresponds to the solution viscosity of 10.0 Pa∙s and is, on the one hand, the maximum permissible given the equipment characteristics and, on the other, is in the recommended concentration range of pumping pickles was taken. The influence of pumping with proposed stabilization solutions on the poultry weight loss during defrosting was revealed. It was proved that due to pumping with proposed stabilization solutions, the poultry weight loss during defrosting significantly reduces (with the maximum selected pumping level of 25 % - by 6.1 % in absolute, by 61.6% - in relative terms), which may indicate achieving a greater reversibility degree of poultry properties after defrosting. Based on the results, the measures to improve the technology of frozen poultry (chicken breast), which consist in additional pumping with stabilization solutions, containing cryoprotective polysaccharides, moisture retaining agents, acidity regulators and antioxidants before freezing were developed.